3414 Association of blood pressure and biochemical knee cartilage composition assessed by T2 relaxation time measurements: Data from the Osteoarthritis Initiative. (27th March 2019) - Ashmeik, Walid; Joseph, Gabby B.; Nevitt, Michael C.; Lane, Nancy E.; McCulloch, Charles E.; Link, Thomas
Abstract : OBJECTIVES/SPECIFIC AIMS: The goal of this study was to investigate the associations of systolic blood pressure (SBP), diastolic blood pressure (DBP) and pulse pressure (PP) with knee articular cartilage composition using magnetic resonance imaging (MRI)-based T2 relaxation time measurements in study participants from the Osteoarthritis Initiative (OAI). METHODS/STUDY POPULATION: In this longitudinal study, 1, 139 participants from the OAI, a multi-center, observational study of the evolution of knee OA, were selected using the following inclusion criteria: right knee Kellgren Lawrence (KL) score (radiographic classification of OA severity) 0-2 indicating no to mild radiographic OA at baseline, no history of rheumatoid arthritis at baseline, available blood pressure measurements at baseline, available T2 measurements in at least three knee compartments at baseline and 48-month follow-up. Linear regression models were performed using standardized values for SBP, DBP and PP as primary predictors and change in cartilage T2 over 48 months, a measure of cartilage matrix quality and degeneration, as the primary outcome. PP was defined as SBP minus DBP. Change in superficial layer and deep layer cartilage T2, which reflect differences in the laminar organization of knee cartilage T2, were also included as outcomes. Statistical models were adjusted for common risk factors for knee OA (baseline age, sex, BMI, KL score) as well as number of currently used anti-hypertensive medications (AHM) reported at baseline. We included AHMs whose primary indication was the treatment of hypertension including beta blockers, angiotensin-converting enzyme (ACE) inhibitors, angiotensin II receptor blockers (ARB), thiazides, chlorthalidone, dihydropyridine calcium channel blockers (CCB) and aliskiren. All predictors, outcomes and covariates (except sex) were analyzed as continuous variables. We included interaction terms in the models to evaluate whether the covariates (age, sex, BMI, KL score, number of AHMs) modified the association of SBP, DBP and PP with cartilage T2. RESULTS/ANTICIPATED RESULTS: The average age of all study participants was 58.8 years (SD ± 8.6) with a higher proportion of men (59.4%), average body mass index (BMI) was 28.3 (SD ± 4.5), average SBP was 122.4 (SD ± 15.4) mmHg, average DBP was 75.5 (SD ± 9.6) mmHg and 469 (38.1%) study participants were taking at least one AHM. Higher baseline DBP was significantly associated with a faster increase in global T2 (0.22 [0.10, 0.35], P < 0.001), global deep layer T2 (0.20 [0.03, 0.36], P < 0.022) and global superficial layer T2 (0.39 [0.20, 0.58], P < 0.001). These associations were significant in both unadjusted and the models adjusted for age, sex, BMI and KL score. No significant associations were found between SBP or PP and cartilage T2 and no significant interactions were found between SBP, DBP, PP and the covariates. DISCUSSION/SIGNIFICANCE OF IMPACT: Higher baseline DBP was associated with a faster increase in knee cartilage T2, suggesting accelerated cartilage degeneration. This association was stronger for the superficial layer of knee cartilage T2 compared to the deep layer. Although further basic mechanistic studies are needed to elucidate the underlying pathophysiology of this relationship, these results suggest lowering DBP may influence knee OA.